Individuals living with cancer in turkey and the covid-19 pandemic - SERT, GÜRKAN (My University, 2022)
The aim of this study is to determine the problems faced by individuals living with cancer (ILCs) in accessing health services during the COVID-19 pandemic in Turkey. This qualitative study\"s sample consisted of 18 volunteer interviewees from 10 cancer-related patient associations in Turkey. Research data were collected by semi-structured interview method. Data collection and analysis were carried out simultaneously. In the sessions where all researchers participated together, the data were coded with a common view, and main and sub-themes were determined. In die analysis of the data the inductive thematic analysis method was applied. Information was gathered under two main themes: compliance with the measures taken and access to health services. Lack of information about nutrition, physical activity, psychological problems, caused by the lockdown and social distance measures taken within the scope of the pandemic should be accepted as problems within the scope of the right of individuals to access health, and additional programs should be prepared to minimize these. Cancer types should be considered in delaying diagnosis, treatment, and controls related to cancer, so that patients are not harmed at least or at all. It is important to ensure that patients do not hesitate to attend diagnosis, treatment, and controls with the anxiety of being infected with COVID-19, both in transportation to health facilities and in terms of preventing transmission in health facilities.

El objetivo de este estudio es determinar los problemas a los que se enfrentan las personas que viven con cáncer (ILC) para acceder a los servicios sanitarios durante la pandemia de COVID-19 en Turquía. La muestra consistió en 18 entrevistados voluntarios de 10 asociaciones de pacientes relacionados con el cáncer en Turquía. Los datos de la investigación se recogieron mediante el método de la entrevista semiestructurada. La recogida y el análisis de los datos se llevaron a cabo simultáneamente. En las sesiones los datos se codificaron con una visión común y se determinaron los temas principales y los subtemas. En el análisis de los datos se aplicó el método de análisis temático inductivo. La información se recogió bajo dos temas principales: el cumplimiento de las medidas adoptadas y el acceso a los servicios sanitarios. La falta de información sobre nutrición, actividad física, problemas psicológicos, causados por el encierro y las medidas de distanciamiento social tomadas en el ámbito de la pandemia, deben ser aceptados como problemas dentro del ámbito del derecho de las personas a acceder a la salud, y se deben preparar programas adicionales para minimizarlos. Los tipos de cáncer deben tenerse en cuenta a la hora de retrasar el diagnóstico, el tratamiento y los controles relacionados, para que los pacientes no se vean perjudicados en lo más mínimo. Es importante asegurar que los pacientes no duden en acudir al diagnóstico, tratamiento y controles con la ansiedad de ser infectados con COVID-19, tanto en el transporte a los centros de salud como en la prevención de la transmisión en estos centros.

O objetivo deste estudo é determinar os problemas enfrentados pelas pessoas que vivem com câncer (PLWC) no acesso aos serviços de saúde durante a pandemia da COVID-19 na Turquia. A amostra consistiu de 18 respondentes voluntários de 10 associações de pacientes relacionados ao câncer na Turquia. Os dados da pesquisa foram coletados usando o método de entrevista semi-estruturada. A coleta e análise de dados foram realizadas simultaneamente. Nas sessões, os dados foram codificados com uma visão comum e os principais temas e subtemas foram determinados. O método de análise temática indutiva foi aplicado na análise de dados. As informações foram coletadas sob dois temas principais: conformidade com as medidas tomadas e acesso aos serviços de saúde. A falta de informação sobre nutrição, atividade física, problemas psicológicos causados pelo confinamento e medidas de distanciamento social tomadas no contexto da pandemia deve ser aceita como problemas dentro do escopo do direito de acesso à saúde das pessoas, e programas adicionais devem ser preparados para minimizá-los. Os tipos de câncer devem ser levados em consideração ao atrasar o diagnóstico, tratamento e check-ups relacionados, para que os pacientes não fiquem em desvantagem mínima. É importante assegurar que os pacientes não hesitem em ir para diagnóstico, tratamento e check-ups com a ansiedade de serem infectados pela COVID-19, tanto no transporte para instalações de saúde quanto na prevenção da transmissão nessas instalações.
Las personas que viven con cáncer en Turquía y la pandemia de covid-19
As pessoas que vivem com câncer na Turquia e a pandemia da covid-19
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Tıp Eğitimi; Sosyal ve Beşeri Bilimler; Sosyoloji; Medicine; Health Sciences; Fundamental Medical Sciences; Medicine Education; Social Sciences and Humanities; Sociology; ETİK; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); TIBBİ ETİK; Klinik Tıp; Klinik Tıp (MED); SOSYAL BİLİMLER, BİYOMEDİKSEL; ETHICS; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); MEDICAL ETHICS; CLINICAL MEDICINE; Clinical Medicine (MED); SOCIAL SCIENCES, BIOMEDICAL; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Individuals living with cancer (ILC); COVID-19 pandemic; healthcare; IMPACT; pessoas vivendo com câncer (PLWC); pandemia de COVID-19; assistência médica; personas que viven con cáncer (ILC); pandemia COVID-19; atención sanitaria; Individuals living with cancer (ILC); COVID-19 pandemic; healthcare